THE USE OF PICTURE SERIES IN IMPROVING STUDENTS’ ENGLISH VOCABULARY MASTERY AT SMA WAHYU MAKASSAR - Andi Ariesta Indar Framesti; Mulyadi Mulyadi; Muthmainnah Mursidin (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2024)
This study aims to assess the effectiveness of the Picture Series method in improving vocabulary mastery of first-grade students at SMA Wahyu Makassar. The research employed a pre-experimental design, utilizing pre-tests and post-tests. The sample comprised 30 randomly selected first-grade students. The findings indicated the implementation of the Picture Series method significantly improved students' vocabulary mastery, with post-test scores showing an average increase from a range of 50 to 63, rising to a range of 85 to 95. Statistical analysis showed a mean difference of 34.00 between pre-test and post-test scores, with a standard deviation of 3.70, a t-value of -50.395, and a p-value of less than 0.001. These results indicated the implementation of the Picture Series method indicated a significant change in student classification, shifting from